Developing Assessment As Learning on Basic Physics Virtual Practicum As An Asessment Instrument of Process And Cognitive Skills on Online-Learning - Setyawarno, Didik; Widodo, Eko; Rosana, Dadan (Journal of Science Education Research, 2022)
This research aimed to i) create and analyze an assessment as learning on basic physics virtual practicum to measure the process and cognitive skills on online-learning, ii) analyze the implementation of the assessment as learning on basic physics virtual practicum to measure the process and cognitive skills on online-learning, and iii) analyze the effectiveness of the implementation of assessment as learning on basic physics virtual practicum to measure the process and cognitive skills on online-learning. This research used Research and Development (R and D) model with 4-D stages consisted of define, design, develop, and disseminate. The result of the research was a product of an assessment as learning, consisting of peer and self-assessment on virtual practicum of basic physic II on online learning. The product was valid based on an analysis of the Aiken formula and empirical study of the Rasch model. The result of the independent t-test sample towards the implementation of the product of assessment as learning, both peer and self-assessment was 0.160, which was higher than 0.5. The result showed that no significant differences occurred in the implementation of assessment as learning, both peer and self-assessment on the practicum of basic physics.